PROSES MEMBANGUN AGENDA SETTING KEBIJAKAN PADA PORTAL BERITA PEMERINTAH DAN KESESUAIANNYA DENGAN AGENDA MEDIA ONLINE - Elfrida, Santhy Verawati (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
Agenda setting is required by the government public relations in disseminating information about the policies that are considered important by the public. The Ministry of Communications and Information Technology as a government public relations (Government Public Relations - GPR) is inseparable from the interests of the public (public agenda) and the media agenda, especially in disseminating strategic issues to the public. One of the media to support the role of the GPR that utilize communications technology and the Internet-based information through news portals InfoPublik. This study aims to examine the process of building agenda setting government policy in the online news portal InfoPublik and analyze the suitability of framing the media agenda kompas.com. The research method with the quantitative and qualitative content analysis using agenda setting theory. Data were collected through interviews and content analysis. The results showed that the governmentâs policy agenda building process conducted by the Ministry of Communications and Information Technology as a government public relations through InfoPublik news portal, has its own governance. Whatâs on the agenda by the Ministry of Communications as a government public relations to strategic issues, especially concerning the implementation of the policy in the presidential election of 2014, related to the public interest (public agenda) agenda through the framing of the news media. Suitability in framing the news in the 2014 Presidential Election themed InfoPublik and Kompas.com have some similarities such as speakers and thematic news.